An Integrated Simulation Model For Effective Planning Of Maintenance Operations For Saudi Arabian Airlines (SAUDIA) - Duffuaa, Salih (2020)
An effective maintenance system is essential for SAUDIA in order to meet its set objectives. These objectives include minimal flight cancellations, minimal delays, minimal repair turn time, and effective utilization of maintenance resources. Tn this paper, the elements of an integrated simulation model for SAUDIA have been described. The integrated model consists of several modules. These are planning and scheduling, organization, supply, quality control and performance measures. The required data and software for such a model have been described. Also, the utility of such a model for SAUDIA has been outlined.